Pemeriksaan Bilirubin Pada Penderita tuberkulosis Paru Yang Dalam Masa Pengobatan Di Rumah sakit Umum Daerah Labuang Baji Makassar - Rosita Rosita; Widarti Widarti; Moh. Basri (Jurnal Media Laboran, 2017)
Tuberculosis (TB) is a disease caused by infection with the Mycobacterium tuberculosis complex. This disease is one of the oldest diseases known to attack humans. This disease usually attacks the lungs (referred to as pulmonary TB), although in one third of cases, other organs are involved. If properly treated with tuberculosis caused by the Mycobacterium tuberculosis complex, which is sensitive to drugs, it can practically be cured. The purpose of this study was to determine the total bilirubin levels in patients with pulmonary tuberculosis who were treated during the period of blood as much as 10 samples of venous blood using the method of purposive sampling. It can be concluded that 50% of the blood samples of pulmonary tuberculosis patients who have been studied for total bilirubin are found to be normal and as many as 50% of the blood samples of pulmonary tuberculosis patients are in an increased state. It is recommended for patients with pulmonary tuberculosis who are in the treatment period to carry out regular checks of liver function tests and take medication regularly and routinely in accordance with the recommended dosage and consume foods that are nutritious enough to increase endurance.